Sistem Monitoring Kesuburan Lahan Pertanian menggunakan Sensor pH, Sensor Suhu, Intensitas Cahaya, dan Kelembapan Tanah Berbasis Internet of Things - Arifin, Samsul; Kurniawati, Neny; Agustiani, Reni; Elsandika, Gabriela (Jurnal Riset Fisika Indonesia, 2025)
This study developed an Internet of Things (IoT)-based soil fertility monitoring system to measure soil pH, soil moisture, and light intensity in real time, specifically for peatland agriculture. The system utilizes pH sensors, soil moisture sensors, and light intensity sensors calibrated with standard measuring instruments to ensure accuracy. Calibration results indicate that the pH sensor has an average error of 0.151%, the soil moisture sensor 1.11%, and the light intensity sensor 6.152%, with the latter exhibiting the highest variation due to environmental factors. Monitoring data shows that soil pH fluctuates more during the day (4.45–4.60) compared to a more stable range at night (4.75–4.80). Soil moisture remains high during the day at 85–90%, while at night, it gradually increases from 25% to 35%. Light intensity fluctuates between 9000–12000 lux during the day and approaches 0 lux at night. With high accuracy and real-time data accessibility, this system can assist farmers in optimizing irrigation, fertilization, and peatland soil management using IoT-based technology, ensuring sustainable agricultural productivity in peatland environments.